Infecção murina por isolados de Leishmania (Viannia) braziliensis: avaliação da participação de leucotrienos endógenos - Bastos, Rosidete Pereira (2008)
The knowledge about immunology of Leishmania (Viannia) braziliensis-murine infection is poorly known, especially concerning innate immune response and the involvement of leukotrienes in the resistance mechanisms. Leukotrienes are lipid mediators of inflammation that activate microbicidal mechanisms in leukocytes. The present study aimed to evaluate the BALB/c and C57Bl/6 murine infection with two L. (V.) braziliensis isolates obtained from cutaneous leishmaniasis patients and the involvement of leukotrienes in the resistance of infection. Thus, IMG3 and RPL5 isolates were identified as L. (V.) braziliensis by using molecular techniques and the in vitro growth of parasites in Grace´s medium (26°C) was evaluated. The time course of lesion after footpad infection was followed in BALB/c and C57Bl/6 mice. C57Bl/6 mice genetically deficient in interferon gamma (IFNγ) were infected to evaluate the relevance of this cytokine in resistance. The parasite burden in draining lymph nodes and spleens was detected by limiting dilution assay. BALB/c- and C57Bl/6-infected footpads were processed after 12 weeks of infection and those from IFNγ-defecient mice after 4 weeks for histopathological analyses. Tissue sections were stained by hematoxylin-eosin. Parasite capacity to induce nitric oxide (NO) was analyzed in RAW 264.7 cell cultures treated or not with IFNγ and lipopolysaccharide (LPS). Nitrites were detected by using Griess reaction. The NO modulation by endogenous leukotrienes was evaluated through treatment of the cultures with a 5-lipoxygenase (5-LO) inhibitor and a leukotriene B4 (LTB4) antagonist. Macrophage leishmanicidal activity against IMG3 isolate was evaluated in thioglycolateelicited peritoneal macrophages of C57Bl/6 mice. In these cultures, NO was inhibited by aminoguanidine. In vivo leukotriene inhibition was achieved by using a 5-LO inhibitor. In vitro-parasite growth profiles were similar and parasites at the 5th day of culture were used to infection. The lesion course was also similar between isolates in both two mouse stains used, but C57Bl/6 mice presented healing after 12 weeks of infection whereas in BALB/c mice the lesion was persistent. In IFNγ-deficient mice there progressive lesions and visceralization in IMG3- as well as in RPL5-infected mice. Corroborating these data, the parasite burden in draining lymph nodes of BALB/c mice was higher than in C57Bl/6 mice after 12 weeks of infection with IMG3, and parasites (IMG3 and RPL5) were identified in about 50% of the IFNγ-deficient mouse spleens. The histopathological analyses showed an intense dermal infiltrate with vacuolated macrophages heavily parasitized in BALB/c mice (12 weeks) an in IFNγ-deficient mice (4 weeks), but not in C57Bl/6 mice (12 weeks), similarly for IMG3 and RPL5. Both isolates IMG3 an RPL5 induced NO production in RAW 264.7 celll cultures presenting synergism with IFNγ. Endogenous leukotrienes did not affect NO production in these cultures. C57Bl/6 peritoneal macrophages activated with IFNγ/LPS killed IMG3 parasites depending on NO release. In vivo inhibition of leukotriene synthesis did not change the course of infection in C57Bl/6 mice infected with IMG3 isolate. The relevant findings are: BALB/c mouse is susceptible to infection with IMG3 an RPL5 isolates whereas C57Bl/6 is resistant; IFNγ is crucial to the control of the infection; the isolates induce NO and this molecule contributes to macrophage leishmanicidal activity; and also the data suggest that endogenous leukotrienes are not involved in the control of L. (V.) braziliensis in C576Bl/6 mouse.